Differential expression profiles of Toll like receptors 20 and 21 in Heteropneustes fossilis in response to infection with Aeromonas hydrophila - Md, Aftabuddin; Mitra, Tandrima; Basu, Arpita (Journal of the Inland Fisheries Society of India, 2020)
The innate immunity serves as the first line of defence against invasion of pathogens in fish. Toll-like receptors (TLRs) play a pivotal role in the innate immunity by specific pathogen-associated molecules that activate immune responses. In the present study, analysis of TLR 20 and TLR 21 in different tissues of healthy catfish, Heteropneustes fossilis showed that the patterns of the gene expression were in the order of spleen > intestine > head kidney > gill and gill > head kidney > liver > spleen > intestine, respectively. Relative transcription of TLR 20 and TLR 21 in different tissues of the fish against bacterial infection investigated by semi- quantitative RT-PCR showed that expression of both TLR 20 and TLR 21 were up-regulated in spleen and intestine whereas that of TLR 21 expression was down-regulated in kidney, gill and liver relative to control fish. Findings of the study suggested that spleen and intestine showed significant alteration in both TLR 20 and TLR 21 expression. Expression of TLR 21 found to be more sensitive than TLR 20 against bacterial infection in fish. Key words Heteropneustes fossilis, Aeromonas hydrophila, TLR 20, TLR 21, Gene expression, Semi-quantitative PCR.